Analisa Kelayakan Investasi Mesin dan Penambahan Tenaga Kerja Serta Penentuan Harga Produk pada UMKM Jamu Wong Jowo - Febita Tri Murani; Siti Muhimatul Khoiroh (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the feasibility of machine investment and additional labor investment at UMKM Jamu Wong Jowo using the capital budgeting method and to calculate the Cost of Goods Manufactured (COGM) using the full costing method. The company faces limited production capacity due to semi-manual processes, resulting in overtime when demand increases. This research employed Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and sensitivity analysis. The results indicate that machine investment is feasible, with a PP of 0.60 years, NPV of Rp160,997,853.18, IRR of 167%, and PI of 6.36. Additional labor investment is also feasible, with a PP of 0.56 years, NPV of Rp23,293,665, IRR of 179%, and PI of 6.82. Sensitivity analysis confirms the resilience of both investments. The COGM after machine investment is Rp7,781 per bottle, indicating improved efficiency and production capacity.